PENGARUH PEMBELAJARAN KOOPERATIF JIGSAW DAN MEDIA PEMBELAJARAN TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA KRISTEN - Leonardo Talakua (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
The purpose of this study was to get empirical data about the effect of cooperative learning jigsaw and the used of media on the Christian Education learning achievement students of SMA Negeri 2 Ambon. The study used quantitative approach with survey design. Population of this researched was all students of SMA Negeri 2 Ambon amount 592 with the sampel was 59 student. Method of data collection used questionnaires and documents, and the questionnaires were tested to 30 student outside the target with validity and reliability test. Hypothesis test used partial test with t test and simultaneous by using SPSS computer program. The result found that there was significant influence between the application of jigsaw learning model to the Christian Education learning achievement of the student of SMA Negeri 2 Ambon. The simple linier line equation formed between the variable of jigsaw learning (X1) with learning media (X2) to the Christian Education learning achievement (Y) was Ῠ=26.219+674 (X1) + 112 (X2). This finding indicated that there was a positive and significant influenced 74,1% the application of jigsaw cooperative learning model, together with the student’s Christian Education learning achievement of SMA Negeri 2 Ambon in academic year 2017-2018, while the rest equal t0 25,9% was influenced by other variables which is not examined in this research.Key words: cooperative, jigsaw, media, achievement, Christian